Prevalence and assessment of malnutrition among children attending the Reproductive and Child Health clinic at Bagamoyo District Hospital, Tanzania. (December 2016) - Juma, Omar; Enumah, Zachary; Wheatley, Hannah; Rafiq, Mohamed; Shekalaghe, Seif; Ali, Ali; Mgonia, Shishira; Abdulla, Salim
Abstract Background Malnutrition has long been associated with poverty, poor diet and inadequate access to health care, and it remains a key global health issue that both stems from and contributes to ill-health, with 50 % of childhood deaths due to underlying undernutrition. The purpose of this study was to determine the prevalence of malnutrition among children under-five seen at Bagamoyo District Hospital (BDH) and three rural health facilities ranging between 25 and 55 km from Bagamoyo: Kiwangwa, Fukayosi, and Yombo. Methods A total of 63, 237 children under-five presenting to Bagamoyo District Hospital and the three rural health facilities participated in the study. Anthropometric measures of age, height/length and weight and measurements of mid-upper arm circumference were obtained and compared with reference anthropometric indices to assess nutritional status for patients presenting to the hospital and health facilities. Results Overall proportion of stunting, underweight and wasting was 8.37, 5.74 and 1.41 % respectively. Boys were significantly more stunted, under weight and wasted than girls (p -value < 0.05). Children aged 24–59 months were more underweight than 6–23 months (p -value = <0.0001). But, there was no statistical significance difference between the age groups for stunting and wasting. Children from rural areas experienced increased rates of stunting, underweight and wasting than children in urban areas (p -value < 0.05). The results of this study concur with other studies that malnutrition remains a problem within Tanzania; however our data suggests that the population presenting to BDH and rural health facilities presented with decreased rates of malnutrition compared to the general population. Conclusions Hospital and facility attending populations of under-five children in and around Bagamoyo suffer moderately high rates of malnutrition. Current nutrition programs focus on education for at risk children and referral to regional hospitals for malnourished children. Even though the general population has even greater malnutrition than the population presenting at the hospital, in areas of high malnutrition, hospital-based interventions should also be considered as centralized locations for reaching thousands of malnourished children under-five.